1998
DOI: 10.1007/s002449900280
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Hardness on Accumulation and Elimination of Cadmium in Two Aquatic Mosses Under Laboratory Conditions

Abstract: This study investigated the effect of water hardness on the accumulation and elimination of cadmium (Cd) by two aquatic mosses, Fontinalis dalecarlica and Platyhypnidium riparioides, under laboratory conditions. The two mosses were exposed to nominal Cd concentrations of 0, 0.8, 2, and 10 microg . L-1, which includes the concentration range generally found in nature. The influence of three levels of water hardness (very soft: 11.7 mg . L-1; soft: 44.2 mg . L-1; and hard water: 92.3 mg . L-1 as CaCO3) was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…High concentrations of Ca reduce heavy metal toxicity by preventing entrance into the cell just by competing for uptake. Consistently, aquatic moss species accumulated less Cd in harder water (applied as CaCO 3 , Gagnon et al, 1998). On the other hand, green unicellular microalgae were protected against Ni toxicity solely by Mg, not Ca ions (Deleebeeck et al, 2009a (Markich et al, 2006, and citations within).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…High concentrations of Ca reduce heavy metal toxicity by preventing entrance into the cell just by competing for uptake. Consistently, aquatic moss species accumulated less Cd in harder water (applied as CaCO 3 , Gagnon et al, 1998). On the other hand, green unicellular microalgae were protected against Ni toxicity solely by Mg, not Ca ions (Deleebeeck et al, 2009a (Markich et al, 2006, and citations within).…”
Section: Discussionmentioning
confidence: 96%
“…Ca 2+ -ATPase, Markich and Jeffree, 1994). During heavy metal toxicity, high Ca concentrations by competing for uptake into the cell, prevent the entrance of the heavy metals as observed in the Cd accumulation studies in aquatic moss in hard water (applied as CaCO 3 , Gagnon et al, 1998). While in green unicellular microalgae the protective mechanism from Ni toxicity by competition was solely by Mg (Deleebeeck et al, 2009a).…”
Section: Lake Studymentioning
confidence: 98%
“…However, it is known that some environmental factors negatively influence trace element uptake in transplants, i.e. increasing water acidity (Fernandez et al 2006), water hardness (Ferreira et al 2009;Gagnon et al 1998;Wehr et al 1987) and antagonistic interactions among cations on binding sites (Cesa et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…calcium, magnesium and carbonate ions, reduce the toxicity of metal ions. Gagnon et al (1998) reported a reduced uptake of Cd with increasing water hardness in aquatic mosses. The presence of suspended solids, sulphur-containing amino acids and organic materials influence metal toxicity negatively.…”
Section: Bioa V Ailabilitymentioning
confidence: 99%